2023
DOI: 10.1177/17455057231176751
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of menstrual symptoms after Coronavirus disease 2019 vaccination in women with endometriosis

Abstract: Background: Vaccination can have an impact on menstruation, and this impact may be more notable in women with inflammatory gynecological pathologies such as endometriosis. Objectives: We aimed to investigate the impact of mRNA-based SARS-CoV-2 vaccines on menstrual cycle–related symptoms in women with endometriosis and assess the effect of hormonal therapy on potential SARS-CoV-2 vaccination-induced menstrual changes. Design: A total of 848 women who received at least two doses of mRNA-based COVID-19 vaccines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…In contrast, there are also studies reporting reduced occurrence or improvement in their symptoms following COVID-19 vaccination, similar to our results [ 11 , 18 ]. However, the studies focusing on dysmenorrhea or back pain described above are very heterogenous regarding their methods; a few evaluated the intensity of the symptoms [ 16 , 17 ], others compared endometriosis patients vs. health controls [ 16 , 19 ], and only two of these studies followed the same approach that we used here and compared the occurrence of the symptoms before and after immunization [ 11 , 18 ]. The majority of our participants reported dysmenorrhea and back pain less frequently after immunization, but rarely, we also observed the reverse pattern, i.e., dysmenorrhea and back pain after but not prior to immunization, similar to our results regarding changes in menstrual bleeding reported elsewhere [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In contrast, there are also studies reporting reduced occurrence or improvement in their symptoms following COVID-19 vaccination, similar to our results [ 11 , 18 ]. However, the studies focusing on dysmenorrhea or back pain described above are very heterogenous regarding their methods; a few evaluated the intensity of the symptoms [ 16 , 17 ], others compared endometriosis patients vs. health controls [ 16 , 19 ], and only two of these studies followed the same approach that we used here and compared the occurrence of the symptoms before and after immunization [ 11 , 18 ]. The majority of our participants reported dysmenorrhea and back pain less frequently after immunization, but rarely, we also observed the reverse pattern, i.e., dysmenorrhea and back pain after but not prior to immunization, similar to our results regarding changes in menstrual bleeding reported elsewhere [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Comparable data regarding risk factors for emerging back pain after immunization against COVID-19 are rare. One study excluded patients with thyroid disease, others do not report on BMI or thyroid dysfunctions [ 16 , 17 , 18 , 19 ], and one study found no impact of BMI and thyroid disease on changes regarding dysmenorrhea and back pain following immunization against COVID-19 [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations